Digitalization of architectural and urban planning activities in Kazakhstan: transformation of urban space - Mussabayev, Т.Т.; Mussabayeva, А.Т.; Taizhanova, А.А.; Uskembayeva, Ж.М. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
In this article, the authors examine the impact of digitalization of architectural and urban planning activities on the transformation of urban space in Kazakhstan. The study and implementation of digital technologies in these areas, taking into account modern challenges and needs of society, can lead to significant changes in urban space and contribute to its transformation, improve design efficiency, improve the quality and safety of construction, reduce construction time and costs, improve infrastructure and to make urban space more functional and comfortable for its residents. The transformation of urban space in Kazakhstan is an important area of ​​urban development, where digitalization can play a significant role. Transparency of processes in architectural and urban planning activities can be significantly increased thanks to information platforms and digital databases. The purpose of this article is to study modern digital technologies and their impact in the transformation of urban space. In this work, the focus is on the use of geographic information systems (GIS), building information models (BIM). In particular, the authors highlight the possibilities of using the geoportal of the state urban planning cadastre of the Republic of Kazakhstan in transforming urban space. Digital databases help increase the transparency of processes, as they provide storage and exchange of information between project participants and contribute to effective data management. The introduction of such technologies makes it possible to monitor the entire construction process, from the initial design stage to the completion of construction and operation of the facility.